A series of Utterly Improbable, Yet Extraordinary Renditions. - Moten, Fred; Campt, Tina M.; Hardy, Ernest; Akomfrah, John; Shepard, Lucius; Hartman, Dionne; Brand, Dionne; Wynter, Sylvia; Emezi, Akwaeke; Bersani, Leo; Hickey, Dave; Butler, Judith; et al. (Londen : Serpentine Gallery, 2017)
Woods, Frederick ; Leo and Diane Dillon ; Imes, Birney ; Orupabo, Frida ; de Clippel, Catherine ; Riis, Jacob A. ; Henzell, Perry ; Lawson, Deana ; Bearden, Romare; Smith, Ming ; Akomfrah, John ; Hoey, Dana ; Herriman, George ; Marshall, Kerry James ; Adjaye, David ; Sayeed, Mallik Hassan.
black power, black cinema, slave Gordon, Bedford-Stuyvesant neighbourhood, lynching of Jesse Washington, lynching of Michael Donald
catalogus naar aanleiding van de tentoonstellingArthur Jafa: A Series of Utterly Improbable, Yet Extraordinary Renditions, Serpentine Galleries, 8 juni tot 10 september 2017
boek
Keywords: Arthur Jafa